2008
DOI: 10.1074/jbc.m804190200
|View full text |Cite
|
Sign up to set email alerts
|

An Activin/Furin Regulatory Loop Modulates the Processing and Secretion of Inhibin α- and βB-Subunit Dimers in Pituitary Gonadotrope Cells

Abstract: Of all ligands of the transforming growth factor ␤ superfamily, inhibins and activins are a physiologically relevant pair that are functional antagonists of each other. Activin stimulates whereas inhibin blocks follicle-stimulating hormone biosynthesis and secretion from pituitary gonadotrope cells, and together, inhibin and activin control the pituitary gonadal axis essential for normal reproductive function. Sharing a similar ␤-subunit, the secretion of inhibin heterodimers (␣/␤) or activin homodimers (␤/␤) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 32 publications
3
22
0
Order By: Relevance
“…3b), and 56 kDa for free β B subunit and 27 kDa for mature β B subunit (Fig. 3c) were identified in the ovarian lysates, which is generally in accordance with previous reports [20][21][22]. It is noteworthy that the inhibin α antibody was able to detect only the precursor and that it could not detect the mature subunit as it did in other species [20].…”
Section: Expression Level Of Inhibin/activin Subunits Proteins In Wilsupporting
confidence: 76%
“…3b), and 56 kDa for free β B subunit and 27 kDa for mature β B subunit (Fig. 3c) were identified in the ovarian lysates, which is generally in accordance with previous reports [20][21][22]. It is noteworthy that the inhibin α antibody was able to detect only the precursor and that it could not detect the mature subunit as it did in other species [20].…”
Section: Expression Level Of Inhibin/activin Subunits Proteins In Wilsupporting
confidence: 76%
“…Dimerization of the bA or bB peptides with a inhibin (encoded by the Inha gene) followed by cleavage, results in heterodimeric inhibin A and inhibin B, respectively ( Fig. 1A) (Antenos et al 2008). After the pro-proteins are synthesized, the prodomains aid in folding and assembling of their mature peptides, by holding them in a dimerization-competent conformation (Gray and Mason 1990;Walton et al 2009Walton et al , 2012.…”
Section: Processing Of Ligandsmentioning
confidence: 98%
“…After the cleavage by convertases, the proand mature domains remain associated through noncovalent interactions (Antenos et al 2008(Antenos et al , 2011. Activins and inhibins are secreted from the cell in this fashion, protecting the nascent mature dimers from extracellular degradation ( Fig.…”
Section: Processing Of Ligandsmentioning
confidence: 98%
“…To reinforce this hypothesis, our results showed that, in the presence of FSH, exogenous activin-A down-regulates expression of inhibin ßA in cultured goat secondary follicles. In addition, ANTENOS et al (2008) demonstrated that activin-A reduces the levels of inhibin ßA and stimulates endogenous production of inhibin -and ßB-subunit mRNA in gonadotrope cells. Using PCR, inhibin-ßA mRNA expression was detected in the oocyte and somatic cells of rat secondary follicles (ZHAO et al 2001).…”
Section: Discussionmentioning
confidence: 99%